A utilização dos custos da qualidade como sistema de mensuração dos investimentos em recursos humanos - Natal, João Carlos (2010)
Businesses increasingly need evaluate their performance, seeking the best way to ensure the survival, growth and deliver results to shareholders, customers and to market. The increases in revenues and the cost reduction with quality, providing returns to shareholders and keeping customers, have been a constant search for organizations. The goal of this dissertation is to develop a system for calculating for measurement results obtained in the Human Resources business of companies, using of Ordinance 290 of 11/04/1997 as parameter for measuring the results obtained with the lack of training and knowledge in of routines labor. The three examples and the three cases developed in this study demonstrate the applicability of the system of calculation proposed. The values obtained relating to the cost of quality demonstrates the importance its measurement for the decision making in companies. This sense, the application of the calculation system has reached the expected goals, measuring financially the costs of the quality related to the labor routines unfulfilled. At the moment when the managers become aware the costs of quality found in their companies, could improve its process of decision-making, earning the benefits arising from an adequate understanding of the relationships between costs, quality and cost of quality; mainly in relation to reduction in its labor liabilities